Analysis Of Competency, Compensation, And Work Environment On Employee Performance With Satisfaction Employment As An Intervening Variable (Case Study of the Department of Industry, Trade, Energy and Mineral Resources North Sumatra Province) - Cut Maulita; Mesra B (International Journal of Society and Law, 2024)
This study aims to test and analyze the influence of competency (X1), compensation (X2), and work environment (X3) on employee performance (Y) which is mediated by satisfaction (Z). The population in this study was consumers with 120 samples taken. The research was conducted from December 2023 to Januari 2024. This study used quantitative data which was processed using SEM-PLS analysis model with Smart PLS 3.0. application. Data sources used primary data taken directly from respondents and secondary one was obtained from interviews with employees in the Department of Industry, Trade, Energy and Mineral Resources North Sumatra Province. The results of the research show that competence has a positive and significant effect on satisfaction. Compensation has a positive and insignificant effect on satisfaction, the work environment has a positive and insignificant effect on satisfaction. Satisfaction has a positive and insignificant effect on employee performance. The work environment has a positive and significant effect on employee performance. Competency has a positive and significant effect on employee performance. Compensation has a positive and insignificant effect on employee performance.